Subolesin vaccination inhibits blood feeding and reproduction of Haemaphysalis longicornis in rabbits - Seung-Hun Lee (Parasites & Vectors, 2020)
Abstract Background Ticks can transmit numerous tick-borne pathogens and cause a huge economic loss to the livestock industry. Tick vaccines can contribute to the prevention of tick-borne diseases by inhibiting tick infestation or reproduction. Subolesin is an antigenic molecule proven to be a potential tick vaccine against different tick species and even some tick-borne pathogens. However, its effectivity has not been verified in Haemaphysalis longicornis, which is a widely distributed tick species, especially in East Asian countries. Therefore, the purpose of this study was to evaluate the effectivity of subolesin vaccination against H. longicornis in a rabbit model. Methods Haemaphysalis longicornis (Okayama strain, female, adult, parthenogenetic strain) and Japanese white rabbits were used as the model tick and animal, respectively. The whole open reading frame of H. longicornis subolesin (HlSu) was identified and expressed as a recombinant protein using E. coli. The expression was verified using sodium dodecyl sulfate polyacrylamide gel electrophoresis, and the immunogenicity of rHlSu against anti-H. longicornis rabbit serum was confirmed using Western blotting. After vaccination of rHlSu in rabbits, experimental infestation of H. longicornis was performed. Variables related to blood-feeding periods, pre-oviposition periods, body weight at engorgement, egg mass, egg mass to body weight ratio, and egg-hatching periods were measured to evaluate the effectiveness of subolesin vaccination. Results The whole open reading frame of HlSu was 540 bp, and it was expressed as a recombinant protein. Vaccination with rHlSu stimulated an immune response in rabbits. In the rHlSu-vaccinated group, body weight at engorgement, egg mass, and egg mass to body weight ratio were statistically significantly lower than those in the control group. Besides, egg-hatching periods were extended significantly. Blood-feeding periods and pre-oviposition periods were not different between the two groups. In total, the calculated vaccine efficacy was 37.4%. Conclusions Vaccination of rabbits with rHlSu significantly affected the blood-feeding and reproduction in H. longicornis. Combined with findings from previous studies, our findings suggest subolesin has the potential to be used as a universal tick vaccine.